2021
DOI: 10.1111/cpr.12980
|View full text |Cite
|
Sign up to set email alerts
|

Role of crosstalk between endothelial cells and smooth muscle cells in vascular calcification in chronic kidney disease

Abstract: Chronic kidney disease (CKD) is an extremely serious health problem that causes poor health outcomes and substantial social and economic burdens worldwide. The high cardiovascular morbidity and mortality in the CKD population are mainly caused by extensive and progressive vascular calcification (VC). 1,2 Notably, in CKD patients, severe intimal calcification (known as atherosclerotic calcification and thought to originate from atherosclerosis) and medial calcification (known as Mönckeberg's sclerosis) are both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 82 publications
0
16
0
1
Order By: Relevance
“…Vascular calcification is a controllable and reversible pathophysiological process similar to the formation of bone and cartilage. Under the induced stimulation, vascular endothelial cells and smooth muscle cells can differentiate into chondroid cells, accompanied by calcium and phosphorus deposition in the vascular wall [ 42 ]. At present, some proteins such as vitamin K-dependent calcification inhibitory proteins [ 43 ], bone morphogenetic proteins [ 44 ], and sclerostin proteins [ 45 ] have been found to be involved in the regulation of vascular calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular calcification is a controllable and reversible pathophysiological process similar to the formation of bone and cartilage. Under the induced stimulation, vascular endothelial cells and smooth muscle cells can differentiate into chondroid cells, accompanied by calcium and phosphorus deposition in the vascular wall [ 42 ]. At present, some proteins such as vitamin K-dependent calcification inhibitory proteins [ 43 ], bone morphogenetic proteins [ 44 ], and sclerostin proteins [ 45 ] have been found to be involved in the regulation of vascular calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Also of importance, our mouse model does not recapitulate the environment of chronic kidney disease, which may induce EndMT via inflammation or oxidative stress. 42 Both cell-specific and pan-inhibition of TGF-β signaling showed inhibitory effects on ECM deposition. These data suggest that differences in AVF wall thickness are attributable to the effects of TGF-β on SMC proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have gradually found that ECs also have the potential to undergo osteochondrogenic differentiation to promote vascular calcifications [59]. The expression of ossification-related genes in ECs was previously significantly altered under atherogenic and pro-inflammatory stimuli in vitro [60].…”
Section: Phosphate Ckd-mbd Axis and Neurovascular Dysfunctionmentioning
confidence: 99%